Ceftriaxone absorption enhancement for noninvasive administration as an alternative to injectable solutions - Boubakar Ba (2019)
Copyright © 2018 American Society for Microbiology. All Rights Reserved. Neonatal sepsis is a major cause of infant mortality in developing countries because of delayed injectable treatment, making it urgent to develop noninjectable formulations that can reduce treatment delays in resource-limited settings. Ceftriaxone, available only for injection, needs absorption enhancers to achieve adequate bioavailability via nonparenteral administration. This article presents all available data on the nonparenteral absorption of ceftriaxone in humans and animals, including unpublished work carried out by F. Hoffmann-La Roche (Roche) in the 1980s and new data from preclinical studies with rabbits, and discusses the importance of these data for the development of noninjectable formulations for noninvasive treatment. The combined results indicate that the rectal absorption of ceftriaxone is feasible and likely to lead to a bioavailable formulation that can reduce treatment delays in neonatal sepsis. A bile salt, chenodeoxycholate sodium salt (Na-CDC), used as an absorption enhancer at a 125-mg dose, together with a 500-mg dose of ceftriaxone provided 24% rectal absorption of ceftriaxone and a maximal plasma concentration of 21 g/ml with good tolerance in human subjects. The rabbit model developed can also be used to screen for the bioavailability of other formulations before assessment in humans.